Пассивный датчик на поверхностных акустических волнах для дистанционного контроля параметров - Karapetyan, G. Ya.; Kataev, V. F. (PE "Politekhperiodika", Book and Journal Publishers, 2006)
A passive sensor based on surface acoustic waves (SAW) is proposed for wireless remote monitoring of physical parameters such as pressure, temperature, humidity, and radiation background. The use of such sensors makes it possible to eliminate transmitters and power sources that are currently required for active radio‑signal‑based sensors.